Occurrence of critical driver's behavior as a result of alcohol intoxication - Jelen, Karel; Soumar, Libor; Fanta, Ondrej (Neuro endocrinology letters, 2011)
OBJECTIVE: Operator's movements are one of the areas where variability is undesirable. Vehicle driving is probably the most frequent operator movement in society where errors can result in serious social, medical and economic consequences. In this article we focused on the influence of moderate alcohol intoxication (less then 1.0 g/kg) on right hand movement variability during manual gear selection and on driving ability. METHODS: The test took place in a laboratory setup in a passenger vehicle simulator. Simulated traffic lights were used to stop the car and hand movement was measured by kinematical analysis with the use of a motion capture system. RESULTS: Large variability in blood alcohol concentrations were observed as well as large intra-individual hand movement variability and reaction time to visual stimulus. DISCUSSION: The findings are somewhat ambiguous. Research outcomes did not confirm the hypothesis about the impact of moderate alcohol intoxication on movement variability. On the other hand, in some cases the observed data indicate critical behavior regarding safe driving and response to particular traffic situations.
Keywords: látky tlumící činnost CNS; Humans; chování; dospělí; ethanol; Automobile Driving; lidé; otrava alkoholem; Adult; Central Nervous System Depressants; řízení motorových vozidel; Reaction Time; Male; User-Computer Interface; Behavior; reakční čas; uživatelské rozhraní počítače; motorické dovednosti; Alcoholic Intoxication; Ethanol; mužské pohlaví; Motor Skills